High-density lipoprotein-mimicking nanodiscs carrying peptide for enhanced therapeutic angiogenesis in diabetic hindlimb ischemia. (April 2018) - Park, Hyun-Ji; Kuai, Rui; Jeon, Eun Je; Seo, Yoojin; Jung, Youngmee; Moon, James J.; Schwendeman, Anna; Cho, Seung-Woo
Abstract: Therapeutic strategies using endogenous stem cell mobilizer can provide effective cell-free therapy for addressing various ischemic diseases. In particular, substance P (SP) exhibited therapeutic regeneration by facilitating mobilization of endogenous stem cells from bone marrow to the injured sites. However, its therapeutic effect has been limited due to short half-life and rapid degradation of administered SP peptides in vivo . Here we sought to develop high-density lipoprotein (HDL)-mimicking nanodiscs conjugated with SP (HDL-SP) in order to increase the in vivo half-life, bone marrow targeting, and therapeutic efficacy of SP for the treatment of diabetic peripheral ischemia. Conjugation of SP onto HDL nanodisc led to remarkable ∼3215- and ∼1060-fold increase in the ex vivo and in vivo half-lives of SP, respectively. Accordingly, HDL-SP nanodiscs improved retention of SP in bone marrow after systemic administration, leading to efficient mobilization of stem cells from bone marrow into blood circulation and reduction of systemic inflammation. Consequently, nanodisc based SP peptide delivery promoted blood vessel formation, blood perfusion recovery and markedly improved limb salvage in diabetic hindlimb ischemia model relative to administration of free SP without nanodisc modification. Therefore, HDL-SP nanodisc can provide a novel strategy for the treatment of diabetic ischemia and HDL nanodisc modification could be potentially useful for the extension of plasma circulation of other labile peptides.